simplifying square roots
This topic has expert replies

 Senior  Next Rank: 100 Posts
 Posts: 64
 Joined: 01 Aug 2009
 Thanked: 5 times
 Followed by:1 members
 GMAT Score:740
(1+ root 3)^2 = 1+3+ (2 root 3)
= 4 + 2 root3
= 2( 2+root 3)
=> 1 + root 3 = (root 2) ( root( 2+ root 3)) ...
Substitute this value of (1 + root3) in the above expression
we get,
(root 2) ( root(2+ root3))*( root(2 root 3)) = (root 2) (root( 43))
{ using (ab)(a+b) = (a^2  b^2) }
So answer= (root 2)
Now, can we have the OA please :roll:
= 4 + 2 root3
= 2( 2+root 3)
=> 1 + root 3 = (root 2) ( root( 2+ root 3)) ...
Substitute this value of (1 + root3) in the above expression
we get,
(root 2) ( root(2+ root3))*( root(2 root 3)) = (root 2) (root( 43))
{ using (ab)(a+b) = (a^2  b^2) }
So answer= (root 2)
Now, can we have the OA please :roll:
MS

 Master  Next Rank: 500 Posts
 Posts: 231
 Joined: 12 Apr 2007
 Thanked: 5 times
 Followed by:1 members
square the whole expression  thats it.
we get (after squaring)
(1+3+2âˆš3) (2âˆš3) = 2
so answer is âˆš2
we get (after squaring)
(1+3+2âˆš3) (2âˆš3) = 2
so answer is âˆš2

 Legendary Member
 Posts: 752
 Joined: 17 May 2009
 Location: Tokyo
 Thanked: 81 times
 GMAT Score:680
one, OA is "official answer".GambitOS wrote:OA is 2.
a. (1+root3)=(root1+root3)=(root4)=2
b. (root(2root3))=(root(root4root3)=(root1)=1
So 2*1=2
so when you give your answer don't say that it's the OA until you are sure that it's the OA
now,
(root1+root3)=(root4)=2Wrong
(root1 + root3) is not equal to root(1+3)
root(root4root3)=(root1)=1wrong
(root4root3) is not equal to root(43)
The powers of two are bloody impolite!!